Hybrid IP/SDN routing for inter-data center communications - Pereira, Vítor Manuel Sá (2019)
Internet Service Providers (ISPs) and dedicated inter-Data Center Wide Area Networks have been exploring Software-Defined Networking (SDN) features to achieve a high utilization of the available resources. This work proposes a scalable hybrid IP/SDN routing model, and optimization procedures fostered by Evolutionary Computation algorithms, to achieve near optimal network resources utilization under changing traffic requirements.